(untitled) (Baghdad Science Journal, 2024)
Acute myeloid leukemia is the most common hematological malignancy in adults. The uncontrolled proliferation of non-differentiating myeloid progenitors is a hallmark of this illness. Mutant cells form when DNA damage cannot be repaired by the cell’s repair mechanisms. One of the DNA repair mechanisms, the base excision repair pathway. The study involved 70 patients with acute myeloid leukemia (37 females and 33 males) as well as 30 apparently healthy individuals as a control group. The gSYNCTM DNA Extraction Kit from Geneaid/Taiwan was used to extract DNA from entire blood samples from the study groups. The Restriction Fragment Length Polymorphism-PCR method was used to identify the APE1 gene’s (rs1130409; Aspl48Glu, T/G in Exon 5) polymorphism. In genetic analysis, it was shown that an increase in the T/ T genotype and the T allele in the APE1 codon 148 polymorphisms play a protective role in AML, and that an increase in the G/G genotype and G allele could be associated with acute myeloid leukemia risk. The polymorphism of APE1 gene at rs1130409 revealed TG genotype and G allele as the most frequent and higher significant (P<0.05) in AML patients compared to the control group. The sequence of the studied region showed that the restriction site of the restriction enzyme is indicated by a site of diversity that is present in the GATC sequencing and transitions to the GAGC sequencing when a nucleotide change (T to G) actually occurs. Our findings suggest that the APE1 rs1130409 polymorphism may be associated with acute myeloid leukemia susceptibility in Iraqi patients. It was discovered that the polymorphic marker 148 Glu> Asp of the APE1 gene was associated with the development of AML. Allele T and genotype T/T carriers have a lower risk of developing AML, whereas allele carriers G have an increased risk.